On the One-Point Model for the Productivity Evaluation in Jingbian Sector of Yan’an Gas Field - Er-hu, Liu; Yang-yang, Liu; Li-jun, Gao; De-sheng, Zhou; Xiong, Liu; Jin-ze, Xu (Frontiers in Earth Science, 2021)
The productivity equation of a gas well is,in the final analysis,an expression that describes the relationship between the production of a gas well and its bottom-hole flowing pressure. There are two kinds of productivity equation in common use at present,binomial productivity equation and exponential productivity equation. Combined with the modified isochronal well test,the test data is interpreted,and it is found that the open flow rates calculated by the two productivity equations are basically the same when the pressure difference at the test point is large,and the deviation of the exponential productivity equation is large when the pressure difference at the test point is small. Using binomial productivity equation and modifying isochronous well test,the single point deliverability formula for the Jingbian sector of Yan 'an gas field is established .The field experience formula and production data are used to verify it,The average errors are 2.59% and 7.12% respectively,and the coincidence rate of productivity evaluation is 90%.The one-point productivity formula established has high precision and is suitable for productivity analysis of gas wells in palaeozoic reservoirs in Jingbian sector of Yan 'an gas field. This paper provides insights into the one-point productivity evaluation and its future application in gas field.